A novel approach based on the ultrasonic-assisted microwave method for the efficient synthesis of Sc-MOF@SiO2 core/shell nanostructures for H2S gas adsorption: A controllable systematic study for a green future - Muzammil, Khursheed; Solanki, Reena; Alkaim, Ayad F.; Romero Parra, Rosario Mireya; Lafta, Holya A.; Jalil, Abduladheem Turki; Gupta, Reena; Hammid, Ali Thaeer; Mustafa, Yasser Fakri (Frontiers in Chemistry, 2022)
In this work, for the first time, novel Sc-MOF@SiO2 core/shell nanostructures have been synthesized under the optimal conditions of ultrasonic-assisted microwave routes. The final products showed small particle size distributions with homogeneous morphology (SEM results), high thermal stability (TG curve), high surface area (BET adsorption/desorption techniques), and significant porosity (BJH method). The final nanostructures of Sc-MOF@SiO2 core/shell with such distinct properties were used as a new compound for H2S adsorption. It was used with the systematic investigation based on a 2K−1 factorial design, which showed high-performance adsorption of about 5 mmol/g for these novel adsorbents; the optimal experimental conditions included pressure, 1.5 bar; contact time, 20 min; and temperature, 20°C. This study and its results promise a green future for the potential control of gas pollutants.